2017
DOI: 10.3389/fmicb.2017.00515
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Potential Applications of Cyanobacteria and Algal Metabolites in Biology, Agriculture and Medicine: Current Status and Future Prospects

Abstract: Cyanobacteria and algae having complex photosynthetic systems can channelize absorbed solar energy into other forms of energy for production of food and metabolites. In addition, they are promising biocatalysts and can be used in the field of “white biotechnology” for enhancing the sustainable production of food, metabolites, and green energy sources such as biodiesel. In this review, an endeavor has been made to uncover the significance of various metabolites like phenolics, phytoene/terpenoids, phytols, ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
222
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(235 citation statements)
references
References 469 publications
(398 reference statements)
1
222
1
11
Order By: Relevance
“…Another field of interest is the production of phytohormones, as it has been demonstrated that different genus of cyanobacteria and algae accumulate and release a diverse group of phytohormones that are involved in plant growth and development [48]. Phytohormones, including auxin, abscisic acid, cytokinin, ethylene (ET), and gibberellins, have been found in a broad spectrum of microalgal lineages.…”
Section: Uses Of Microalgae and Cyanobacteria For Cosmetic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another field of interest is the production of phytohormones, as it has been demonstrated that different genus of cyanobacteria and algae accumulate and release a diverse group of phytohormones that are involved in plant growth and development [48]. Phytohormones, including auxin, abscisic acid, cytokinin, ethylene (ET), and gibberellins, have been found in a broad spectrum of microalgal lineages.…”
Section: Uses Of Microalgae and Cyanobacteria For Cosmetic Applicationsmentioning
confidence: 99%
“…It is also worth mentioning the research in obtaining micosporine-like amino acids from cyanobacteria [51], which are similar to those obtained from macroalgae, for their potential use in sunscreens; and other photo-protective compounds such as scytonemin (a dimer of indolic and phenolic subunits), which is capable of reducing the risk of damage caused by UV light [48].…”
Section: Uses Of Microalgae and Cyanobacteria For Cosmetic Applicationsmentioning
confidence: 99%
“…Ефективність використання мікроелементів організмом визначається рівнем збалансованос ті раціонів щодо поживних і біологічно активних речовин, ступенем засвоєння, депонування та взаємодії мікроелементів між собою [4,8].…”
Section: оригінальні дослідженняunclassified
“…Останнім часом як джерела селену і мікроелементів почали ви-користовувати одноклітинні фотосинтезувальні водорості [9], що як самі є джерелом біологіч но активних речовин, утворених за рахунок внут рішньоклітинного біосинтезу, так і можуть погли-нати та накопичувати екзогенні мікроелементи, включаючи їх до складу, насамперед, пігментів, білків і ліпідів [8].…”
Section: оригінальні дослідженняunclassified
“…The cyanobacterium Arthrospira platensis is an outstanding sunlight-driven cell factory that has the ability to convert carbon dioxide into high added value metabolites (Singh et al, 2017). This photosynthetic cyanobacterium have received much attention for high value metabolites such as α-tocopherol, β-carotene, lutein and γ-linolenic acid (Esquivel-Hernández et al, 2016;Sosa-Hernández et al, 2019) and bioactive effects such as antiproliferative, antitumor, antifungal, antibacterial, antimalarial, antiviral, antimycotic, cytotoxicity, multi-drug resistance reversers and immunosuppressive agents (Dixit & Suseela, 2013;Ediriweera et al, 2017;Kumari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%